Effect of Binder on Bioceramic Mechanical Properties and Surface Roughness when Milling - Sabri, Nadim; Rafai, Noor Hakim (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Under pressing during milling, the study focuses on the impact of binders on the surface roughness of bioceramics, specifically hydroxyapatite (HAp). Finding the ideal binder percentage in HAp bioceramics to attain the required surface roughness is the main goal. The application of polyvinyl alcohol (PVA) and polyethylene glycol (PEG) as binders at different concentrations is investigated in this work. The process comprises prepping the HAp samples, combining them with binders, compressing, and sintering them, and then milling them under carefully monitored conditions. Next, the machined parts’ surface roughness is measured. The goal of the research is to optimise the binder composition of bioceramic implants in order to improve their mechanical properties and surface integrity. By shedding light on the processing variables that affect the functionality and calibre of bioceramic implants, this study advances the field of biomaterials.